Impacto de la violencia intrafamiliar de los adolescentes del cantón Machala periodo 2022 – 2023 - De La Cruz Díaz, Emely Arley (Machala: Universidad Técnica de Machala, 2023)
This investigation examines domestic violence, w Impact of domestic violence on the social relationships of adolescents in the Machala canton period 2022 / 2023 Which has allowed high levels of crimes to be recorded in Ecuador and the entire world; With the passage of time, they have deepened until they have become one of the most harmful and recurrent acts for harmonious coexistence in society. Within this we find the various acts of intimidation, exercised in the first instance against women, followed by children and adolescents who live within the home, worldwide one in three women are victims of physical and sexual violence, most of which are caused by their partners or cohabitants. Within this research on violence it has been found that worldwide there is a 38% increase in murders of women that are carried out by their partners or cohabitants, 6% of them refer to having suffered sexual assaults by other people who are not their cohabitants, this is what our beloved Ecuador unfortunately experiences a thousand times you hear news of murders, whether in children, adolescents or even women, all of this has been based on abuse in order to achieve the result they want so much, subjecting the victim and thus having control of the situation, arises in the creation of a gap of great inequalities, threatening the lives of other people due to their gender difference and machismo. Machala is a canton that belongs to the province of El Oro, where according to the Correo newspaper (2022) it was reported that there is an average of 318 emergency calls due to domestic violence, according to statistical data in El Oro they respond to 14 daily calls of which 6 correspond to Machala. It should be noted that from the scope of the conception of the theory of family development, domestic violence is seen as a diverse social problem that covers areas from human rights, comprehensive development, public health throughout the world, since it affects the normal performance and interaction of people with their family, social, cultural and economic environments, which deteriorates the local social fabric, that the subject is formed from childhood from the family environment in his first forms of interaction with his peers and his social codes of integration to their established dynamics of conduct or common behavior, in an environment of equality, respect and peace, necessary to develop their multiple activities or actions, however this balance is interrupted by violence within the home, within the framework conceptually we talk about human violence and in it domestic violence, at least three theoretical approaches can be identified that try to find its origin and causality: Biological theories. who consider violence as an instinct that manifests itself individually and socially isolated from culture, morality and rationality as determining factors of it. Domestic violence as the behavioral condition of the exercise of unequal power imposed by force of the man on the other members of the home, through physical, psychological, sexual, emotional abuse. In this sense, coexistence within the family is essential to mark and determine the collective behaviors of the socialization practices that are generated and reproduced in the family, as a manager of its own and shared identity for development and acceptance in its community. same year they reached 22%. These figures show that homes have become the places or spaces where violence is generated with greater intensity and consequences on the emotional structure, health and social development of adolescents and their mothers, which determines that 6 of every 10 people in this period have suffered some type of manifestation of violence at ages ranging between 1 and 14 years of age, disrupting their normal development and integration into society. According to the 2020 report of the Economic Commission for Latin America and the Caribbean - ECLAC, it mentions that, in the Latin American region, 50% of the population under 18 years of age has been a victim of domestic or family violence, the same as It is usually caused by the household members themselves. Domestic violence is truly considered a social and public health problem, which directly affects the psyche and emotional stability of adolescents in their stage of development and training, being essential an environment of peace and balance for the learning and practice of the values and behaviors for their relationship and interaction with society. It is essential that, from its comprehensive approach, the State develop policies and programs to prevent violence, where murder and organized crime generate in Ecuador
La presente investigación, examina La presente investigación examina el Impacto de violencia intrafamiliar en las relaciones sociales de los adolescentes del cantón Machala periodo 2022 / 2023 Lo cual a permitido registrar altos niveles de crímenes en Ecuador y el mundo entero; con el pasar del tiempo se han ido profundizando hasta convertirse en uno de los actos más nocivos y recurrentes para una convivencia armónica en la sociedad, dentro de ello encontramos las varías varios hechos de intimidación, ejercidos en primera instancia a la mujer, seguido por los niños y adolescentes que viven dentro del hogar, a nivel mundial una de cada tres mujeres son víctimas de violencia física y sexual, en su mayoría son provocadas por sus parejas o conviviente. Dentro de esta investigación sobre la violencia se ha encontrado que a nivel mundial existe un incremento del 38% de asesinatos de mujeres que son realizados por su parejas o convivientes, el 6% de hace referencia de haber sufrido agresiones sexuales por otras personas que no son sus convivientes, esto es lo que lastimosamente vive nuestro querido Ecuador una y mil veces escuchas noticias de sucesos de asesinatos ya sean en niños adolescentes incluso mujeres, todo esto se a basado en el maltrato para así conseguir el resultado que tanto quieren, sometiendo a la víctima y así tener el control de la situación, surge en la creación de una brecha de grandes desigualdades atentando contra la vida de las demás personas por su diferencia de género y machismo. Machala es un canton que pertenece a la provincia de El Oro, donde según diario Correo 2022 informaba que existe un promedio de 318 llamadas de emergencias por violencia intrafamiliar, según datos estadísticos en El Oro atienden a 14 llamadas diarias de las cuales 6 corresponden a Machala. Cabe recalcar que desde el ámbito de la concepción de la teoría del desarrollo familiar, la violencia intrafamiliar es vista como un problema social, diverso que abarca ámbitos desde los derechos humanos, desarrollo integral, salud pública en todo el mundo, ya que afecta el normal desempeño e interacción de las personas con sus entornos familiar, social, cultural y económico, que deteriora el tejido social local, que el sujeto, es formado a partir de la infancia desde el ámbito familiar en sus primeras formas de interacción con sus semejantes y sus códigos sociales de integración a sus dinámicas establecidas de conducta o comportamiento común, en un ambiente de igualdad, respeto y paz, necesarios para desarrollar sus múltiples actividades o acciones, sin embargo este equilibrio es interrumpido por la violencia al interior del hogar,en el marco conceptual se habla sobre la violencia humana y en ella la violencia intrafamiliar, se pueden identificar al menos tres enfoques teóricos que tratan de hallar su origen y causalidad: Las teorías biológicas que consideran a la violencia como un instinto que se manifiesta de manera individual como socialmente aislado de la cultura, la moral y la racionalidad como factores determinantes de la misma. La violencia intrafamiliar como la condición de comportamiento del ejercicio del poder desigual e impuesto por la fuerza del hombre a los demás miembros del hogar, a través del maltrato físico, psicológico, sexual, emociona. En este sentido la convivencia en el seno familiar es fundamental para marca y determinar los comportamientos colectivos de las prácticas de socialización que se generan y reproducen en la familia, como gestora de una identidad propia y compartida para el desenvolvimiento y aceptación en su comunidad. mismo año que alcanzaron el 22%. Estas cifras ponen en evidencia que los hogares se han convertido en los sitios o espacios donde se genera la violencia con mayor intensidad y consecuencias en la estructura emocional, salud y desarrollo social, de los más adolescentes y sus madres, lo que determina que 6 de cada 10 personas en este periodo han sufrido algún tipo de manifestación de violencia en edades que oscilan entre 1 y 14 años de edad, trastocando su normal desarrollo e integración a la sociedad. Según el informe 2020 de la Comisión Económica para América Latina y el Caribe - CEPAL, menciona que, en la región de América Latina, la población menor de 18 años, ha sido víctima en un 50% de violencia doméstica o familiar, la misma que por lo general es provocada por los mismos miembros del hogar. La violencia intrafamiliar es considerada realmente como un problema social y de salud pública, lo que afecta directamente la psiquis y estabilidad emocional de los adolescentes en su etapa de desarrollo y formación, siendo fundamental, un ambiente de paz y equilibrio para el aprendizaje y práctica de los valores y conductas para su relación e interacción con la sociedad. Es primordial que, desde su enfoque integral, el Estado desarrolle políticas y programas de prevención de la violencia, donde el asesinato y el crimen organizado generan en el Ecuador.
Keywords: VIOLENCIA; MACHALA; FAMILIA; ADOLESCENTE